2022
DOI: 10.1177/08982643211063338
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Association of Late-Life Visual and Hearing Difficulty and Cognitive Function: The Role of Social Isolation

Abstract: Objectives Sensory impairments are prevalent among older adults and have been associated with cognitive challenges in later life, yet mechanisms are less well understood. We examined the mediating role of social isolation in the longitudinal relationship between self-reported sensory difficulty and impaired cognitive functioning among older adults. Methods Data were taken from the NHATS Study, an annual survey of Medicare beneficiaries’ age ≥ 65. Participants ( N = 6,338) provided data at Rounds 5, 6, and 7 (2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…No indirect associations were significant for VI or HI, predicting cognitive functioning through social isolation. Past research has identified social isolation as an important mediator of the relationship between sensory impairments and cognitive functioning [27]. This non-finding may, again, be evidence of an effect modification by culture, owing to familism.…”
Section: Summary Of Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…No indirect associations were significant for VI or HI, predicting cognitive functioning through social isolation. Past research has identified social isolation as an important mediator of the relationship between sensory impairments and cognitive functioning [27]. This non-finding may, again, be evidence of an effect modification by culture, owing to familism.…”
Section: Summary Of Findingsmentioning
confidence: 89%
“…This association has been shown to significantly accelerate brain aging and contribute to earlier death [26]. Longitudinal, population-based research has identified social isolation as a mechanism linking sensory impairment with cognitive functioning among a national sample of older adults with sensory impairments in the U.S. [27].…”
Section: Introductionmentioning
confidence: 99%
“…In participants with dual hearing and vision loss, there is a significantly increased risk of both developing Alzheimer's disease and non-specific cognitive decline and dementia compared to a control population with normal sensory function [30][31][32]. For most studies, this effect appears to be more important for those with visual than hearing impairment [31,33] though some indicated the opposite [34].…”
Section: Introductionmentioning
confidence: 99%
“…There is established evidence of the associations between vision impairment and physical, cognitive, psychological, and social functioning, as well as independence, and well-being. [8][9][10][11][12][13][14] Longitudinal studies have shown that vision impairment is a risk factor associated with cognitive decline, 8 reduced physical activity, 9 increased falls and fratures, 10 depression, 11 social isolation, 12 frailty, 15 and mortality. 13 Our previous work conceptualizing a model on how vision impairment challenges successful aging highlights how the impact of vision impairment on aging outcomes can be addressed at multiple intervention points.…”
mentioning
confidence: 99%
“…To generate this body of evidence, research efforts must move beyond the confines of clinical ophthalmology. There is established evidence of the associations between vision impairment and physical, cognitive, psychological, and social functioning, as well as independence, and well-being . Longitudinal studies have shown that vision impairment is a risk factor associated with cognitive decline, reduced physical activity, increased falls and fratures, depression, social isolation, frailty, and mortality .…”
mentioning
confidence: 99%